Research Mapping of Arabic Reading Skills: A Scopus-Based Bibliometric Analysis, Systematic Review, and Pedagogical Implications for Arabic Language Teaching - Ahmad Fadhil Ryan Pratama; Amin Nasir; Habib Maulana Maslahul Adi; Syafa Bachrun Naja Al-amin (Journal of Arabic Language Teaching, 2026)
Research on Arabic reading skills has increased substantially in response to the growing demand for Arabic proficiency in academic, religious, and foreign language education; however, existing studies remain fragmented and lack an integrated overview. Bibliometric analysis combined with a Systematic Literature Review (SLR) provides a comprehensive framework for mapping publication trends, collaboration networks, research themes, and knowledge gaps. This study aims to analyze global research trends on Arabic reading skills during 2016–2025 and identify their pedagogical implications for Arabic as a Foreign Language (AFL) instruction. Employing a qualitative descriptive design, the study analyzed 105 Scopus-indexed journal articles selected through the PRISMA protocol. Data were collected from the Scopus database and examined using VOSviewer through co-occurrence, co-authorship, citation, and thematic analyses. The findings reveal a significant increase in publications after 2019, five dominant research clusters, and limited international collaboration, with notable gaps in higher education and non-Arab AFL contexts. The study concludes that Arabic reading research has become increasingly interdisciplinary but requires stronger international collaboration, broader contextual research, and more integrative pedagogical frameworks to support future Arabic language teaching and research. Penelitian mengenai keterampilan membaca bahasa Arab mengalami peningkatan signifikan seiring meningkatnya kebutuhan penguasaan bahasa Arab dalam konteks akademik, keagamaan, dan bahasa asing, namun kajian yang ada masih terfragmentasi dan belum memberikan gambaran yang komprehensif. Analisis bibliometrik yang dipadukan dengan Systematic Literature Review (SLR) memberikan kerangka untuk memetakan tren publikasi, kolaborasi, tema penelitian, dan kesenjangan riset. Penelitian ini bertujuan memetakan perkembangan penelitian global tentang keterampilan membaca bahasa Arab periode 2016–2025 serta mengidentifikasi implikasinya bagi pembelajaran Arabic as a Foreign Language (AFL). Penelitian menggunakan pendekatan deskriptif kualitatif dengan analisis bibliometrik dan SLR terhadap 105 artikel jurnal terindeks Scopus yang dipilih melalui protokol PRISMA. Data dikumpulkan dari basis data Scopus dan dianalisis menggunakan VOSviewer melalui analisis co-occurrence, co-authorship, sitasi, dan tema. Hasil penelitian menunjukkan peningkatan publikasi sejak 2019, terbentuknya lima klaster tema utama, serta masih terbatasnya kolaborasi internasional dan penelitian pada konteks pendidikan tinggi serta AFL di negara non-Arab. Penelitian ini menyimpulkan bahwa kajian keterampilan membaca bahasa Arab berkembang menjadi bidang interdisipliner, namun memerlukan kolaborasi global, penelitian yang lebih kontekstual, dan kerangka pedagogis yang lebih integratif.